2001
DOI: 10.1021/jf010227t
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Resonance Studies of Free Radicals in γ-Irradiated Soybean Paste

Abstract: Free radicals in gamma-irradiated soybean paste were investigated by electron spin resonance (ESR) spectroscopy to determine the effect of temperature (77-296 K) and moisture content (1-54%) of samples irradiated at high dose (1-40 kGy). The samples were kept in liquid nitrogen (77 K) during irradiation and subsequent ESR measurements. The spectra shown at 77 K consisted of the hydrogen atom lines at low and high field and complicated symmetric spectrum. By increasing the microwave power, the line shape of ESR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…The group fed irradiated soybeans had elevated levels of oxidation in liver lipids, DNA oxidative damage, as well as myelin figures and swollen mitochondria in parietal and intestinal epithelial cells. Lee and others (2001, 2002) demonstrated that dry soybean paste exposed to γ‐irradiation resulted in trapped radicals. Farrow and Davis (1990) found that an increased risk of pancreatic cancer was associated with increased protein intake in general in men.…”
Section: Resultsmentioning
confidence: 99%
“…The group fed irradiated soybeans had elevated levels of oxidation in liver lipids, DNA oxidative damage, as well as myelin figures and swollen mitochondria in parietal and intestinal epithelial cells. Lee and others (2001, 2002) demonstrated that dry soybean paste exposed to γ‐irradiation resulted in trapped radicals. Farrow and Davis (1990) found that an increased risk of pancreatic cancer was associated with increased protein intake in general in men.…”
Section: Resultsmentioning
confidence: 99%
“…All the irradiation experiments were conducted under ambient temperature in the facility rooms, but during electron-only irradiation, temperature increased up to 50°C in the 500 kGy samples for 10 s. It is known that the sample temperature may affect the free radical formation rate (Lee et al , 2001 ) mainly in liquid state and, therefore, the preservation of the activity of the molecules (Kempner et al , 1986 ). However, considering that all our samples were in dry state, and we irradiated them in a narrow stretch of temperatures, the production of free radicals and their effect on the structure of the compounds are expected to be proportional to radiation dose but, mostly, negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Using the combined techniques of on-line high-performance liquid chromatography/electron spin resonance and mass spectrometry (LC/ESR and LC/MS), Qian et al ( , ) identified spin trapped lipid-derived carbon-centered radicals formed in linoleic acid peroxidation and the reactions of two ω-6 polyunsaturated fatty acids (linoleic and arachidonic acids) with soybean lipoxygenase in the presence of α-[4-pyridyl 1-oxide]- N - t -butyl nitrone. Polat and Korkmaz () used ESR spectroscopy to study kinetics of radiation-induced free radical and Mn 2+ signals in γ-irradiated ground soybeans at a temperature range of 130−400 K. Lee et al ( , ) investigated free radicals in γ-irradiated soybean paste by ESR spectroscopy and compared it with those of soybean protein isolate and soybean oil to examine the influences of irradiation dose, moisture content, and heating after irradiation of the free radical concentration and species.…”
Section: Introductionmentioning
confidence: 99%